2018
DOI: 10.3390/ijms19092780
|View full text |Cite
|
Sign up to set email alerts
|

A Dairy-Derived Ghrelinergic Hydrolysate Modulates Food Intake In Vivo

Abstract: Recent times have seen an increasing move towards harnessing the health-promoting benefits of food and dietary constituents while providing scientific evidence to substantiate their claims. In particular, the potential for bioactive protein hydrolysates and peptides to enhance health in conjunction with conventional pharmaceutical therapy is being investigated. Dairy-derived proteins have been shown to contain bioactive peptide sequences with various purported health benefits, with effects ranging from the dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…In LoVo and HT-29 cells, 3 kDa milk induced variation in mitochondrial stability initiated by excessive ROS accumulation [ 16 ]. Of note, when we investigated the role of 3 kDa milk in the miR-27b + cell death mechanism(s), results showed that it enhances the apoptosis and ER-stress induction, in line with previous studies showing synergism among milk bioactive compounds [ 15 , 68 , 69 , 70 ]. In addition, as for lactose intolerant consumers, while previous studies reported that ultrafiltration membrane technology decreased the lactose content of milk [ 71 ], a complete depletion of lactose can be achieved by enzymatic approach.…”
Section: Discussionsupporting
confidence: 88%
“…In LoVo and HT-29 cells, 3 kDa milk induced variation in mitochondrial stability initiated by excessive ROS accumulation [ 16 ]. Of note, when we investigated the role of 3 kDa milk in the miR-27b + cell death mechanism(s), results showed that it enhances the apoptosis and ER-stress induction, in line with previous studies showing synergism among milk bioactive compounds [ 15 , 68 , 69 , 70 ]. In addition, as for lactose intolerant consumers, while previous studies reported that ultrafiltration membrane technology decreased the lactose content of milk [ 71 ], a complete depletion of lactose can be achieved by enzymatic approach.…”
Section: Discussionsupporting
confidence: 88%
“…Further research regarding the role of the CV protective effect of ghrelin would be of great help, including the lowering of BP, the regulation of atherosclerosis, and insulin resistance [46][47][48]. An interesting study recently reported ghrelin-stimulating bioactive peptides derived from casein with potent effects in rats and in vitro [49]. In accordance with our clinical data, another animal study also revealed a decrease in BP after ghrelin administration [50].…”
Section: Adipokines and Inflammationsupporting
confidence: 82%
“…To this end, the authors remarked the expression of GHSR-1a on vagal nerve terminals throughout the small and large intestine. In summary, although further studies are required to better characterize a peptide-mediated ghrelinergic bioactivity in casein hydrolysates, we may remark that the two main milk protein fractions, caseins and whey proteins, can release factors upon digestion which show quite opposite effects on the ghrelinergic system and hence on mechanisms regulating hunger [ 144 ].…”
Section: How Dairy Proteins Can Modulate Food Intake and Glucose Hmentioning
confidence: 99%